2012
DOI: 10.2175/193864712811704071
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Demonstration of the Activated Iron Process for Removing Heavy Metals from Flue-Gas-Desulfurization (FGD) Wastewater

Abstract: The Activated Iron Process (AIP), a novel chemical water treatment platform, was developed for removing various micro-pollutants and impurities from a liquid stream. This integrated treatment system employs certain iron chemistry to create a hybridized reactive solid mixture that comprises three reactive components: zero-valent iron (ZVI) particles with activated surface, redox reactive iron oxide crystalline (FeOx), and certain labile Fe(II) species. The hybrid ZVI/FeOx/Fe(II) system can overcome the surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…(b) Pretreatment : Conventional treatment processes such as the zerovalent iron and adsorption methods have been investigated in FGD wastewater treatment. Huang et al , integrated zerovalent iron, magnetite, and divalent iron materials, designed a four-stage composite zerovalent iron reactor for FGD wastewater treatment, and then tested the removal of Hg and Se on a 5-month-long pilot platform. The effluent results showed that the technology could control Hg and Se below 10 μg/L and 10 ng/L.…”
Section: Controlling Technologies For Solving the Problem Of Volatile...mentioning
confidence: 99%
See 1 more Smart Citation
“…(b) Pretreatment : Conventional treatment processes such as the zerovalent iron and adsorption methods have been investigated in FGD wastewater treatment. Huang et al , integrated zerovalent iron, magnetite, and divalent iron materials, designed a four-stage composite zerovalent iron reactor for FGD wastewater treatment, and then tested the removal of Hg and Se on a 5-month-long pilot platform. The effluent results showed that the technology could control Hg and Se below 10 μg/L and 10 ng/L.…”
Section: Controlling Technologies For Solving the Problem Of Volatile...mentioning
confidence: 99%
“…(b) Pretreatment: Conventional treatment processes such as the zerovalent iron and adsorption methods have been investigated in FGD wastewater treatment. Huang et al 131,132 effluent results showed that the technology could control Hg and Se below 10 μg/L and 10 ng/L. Zhu 133 prepared a magnetic zeolite mercury adsorbent using iron ore from activated fly ash, and the adsorbent achieved 92% Hg 2+ removal under adsorption conditions with a solid-to-liquid ratio of 5 g/L and initial pH of 5.…”
Section: Controlling Technologies For Solving the Problem Of Volatile...mentioning
confidence: 99%
“…A detailed knowledge of the original coal composition is crucial for determining the concentrations of toxic metal cations in the FGD wastewater. The biggest challenge for the electric utility industry is to develop more advanced treatment methods in order to reduce the concentrations of heavy metal cations present in a complex FGD matrix to permissible levels [8].…”
Section: Introductionmentioning
confidence: 99%